Determination of Trust, Financial Literacy, and Investment Decisions on the Millennial Generation in the Sharia Capital Market - Fauzan Fauzan (Journal of Islamic Economics, 2024)
This study aims to examine the relationship between financial literacy, trust, and investment decisions among millennials in the Islamic capital market. The research focuses on young investors' understanding of Islamic financial instruments and how trust in financial institutions influences their investment behavior. Using a quantitative approach with a case study design, data were collected through surveys of 150 respondents and in-depth interviews with active investors. Data analysis was conducted using linear regression and structural equation modeling (SEM) to test the direct and indirect effects between variables. The results showed that financial literacy has a significant influence on investment decisions, with a correlation coefficient of 0.57 (p < 0.01). Trust in Islamic financial institutions also proved to be a critical determinant factor, with an influence coefficient of 0.64 (p < 0.01). Furthermore, financial literacy indirectly affects investment decisions through the mediation of trust (indirect effect = 0.31; p < 0.01). These findings suggest that improving financial literacy and strengthening Sharia supervision can increase millennial participation in Islamic investments. The implications of this research provide insights for regulators and financial institutions to develop more comprehensive financial education programs and build a sustainable investment ecosystem. Recommendations for future research include expanding the study population to Generation Z and exploring other external factors, such as the influence of social media on investment decisions. Thus, this study can serve as a foundation for enhancing financial literacy and developing a more inclusive Islamic capital market.